Imaging Striatal Microglial Activation in Patients with Parkinson’s Disease - Koshimori, Yuko (PLoS One, 2015)
This study investigated whether the second-generation translocator protein 18kDa (TSPO) radioligand, [(18)F]-FEPPA, could be used in neurodegenerative parkinsonian disorders as a biomarker for detecting neuroinflammation in the striatum. Neuroinflammation has been implicated as a potential mechanism for the progression of Parkinson’s disease (PD). Positron Emission Tomography (PET) radioligand targeting for TSPO allows for the quantification of neuroinflammation in vivo. Based on genotype of the rs6791 polymorphism in the TSPO gene, 16 mixed-affinity binders (MABs) (8 PD and age-matched 8 healthy controls (HCs)), 16 high-affinity binders (HABs) (8 PD and age-matched 8 HCs) and 4 low-affinity binders (LABs) (3 PD and 1 HCs) were identified. Total distribution volume (V(T)) values in the striatum were derived from a two-tissue compartment model with arterial plasma as an input function. There was a significant main effect of genotype on [(18)F]-FEPPA V(T) values in the caudate nucleus (p = 0.001) and putamen (p < 0.001), but no main effect of disease or disease x genotype interaction in either ROI. In the HAB group, the percentage difference between PD and HC was 16% in both caudate nucleus and putamen; in the MAB group, it was -8% and 3%, respectively. While this PET study showed no evidence of increased striatal TSPO expression in PD patients, the current findings provide some insights on the possible interactions between rs6791 polymorphism and neuroinflammation in PD.